2018
DOI: 10.1038/s41598-018-35298-3
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Confocal Microscopy detects a Reduction in Corneal Endothelial Cells and Nerve Fibres in Patients with Acute Ischemic Stroke

Abstract: Endothelial dysfunction and damage underlie cerebrovascular disease and ischemic stroke. We undertook corneal confocal microscopy (CCM) to quantify corneal endothelial cell and nerve morphology in 146 patients with an acute ischemic stroke and 18 age-matched healthy control participants. Corneal endothelial cell density was lower (P < 0.001) and endothelial cell area (P < 0.001) and perimeter (P < 0.001) were higher, whilst corneal nerve fibre density (P < 0.001), corneal nerve branch density (P < 0.001) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 50 publications
5
19
2
1
Order By: Relevance
“…This is the first study to show greater corneal nerve loss in patients with recurrent ischemic stroke compared to a 1 st ischemic stroke. This extends our previous findings demonstrating corneal nerve loss in patients with TIA [31] and acute ischemic stroke [32,33]. Individual vascular risk factors such as diabetes, hypertension, smoking, dyslipidemia and metabolic syndrome are associated with the risk of a first and recurrent ischemic stroke [5-7, 13, 43].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This is the first study to show greater corneal nerve loss in patients with recurrent ischemic stroke compared to a 1 st ischemic stroke. This extends our previous findings demonstrating corneal nerve loss in patients with TIA [31] and acute ischemic stroke [32,33]. Individual vascular risk factors such as diabetes, hypertension, smoking, dyslipidemia and metabolic syndrome are associated with the risk of a first and recurrent ischemic stroke [5-7, 13, 43].…”
Section: Discussionsupporting
confidence: 85%
“…MRI studies have shown that structural alterations including white matter hyperintensities, lacunes and microbleeds are associated with an increased risk of recurrent ischemic stroke [9,13,15]. We have previously shown a loss of corneal nerves in subjects with a major ischemic stroke compared to controls and an association between corneal nerve loss with HbA1c and triglycerides [32,33]. In the present study, despite age, BMI, HbA 1c , lipids, BP and use of medications to treat blood pressure and lipids being comparable between those with recurrent stroke and 1 st stroke, there was greater corneal nerve damage in patients with recurrent compared to 1 st stroke.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…können auch durch andere Primärerkrankungen hervorgerufene Veränderungen des SNP und des Endotheliums untersucht werden, wie z. B. die Auswirkungen von ischämischen Schlaganfällen [5,11].…”
Section: Digitale Bildverarbeitung Und Tiefe Neuronale Netze In Der Aunclassified
“…Quantitative sensory testing to evaluate vibration and thermal perception thresholds are easy to perform, but lack reproducibility, especially in children and skin or nerve biopsies are invasive procedures [12]. Corneal confocal microscopy (CCM) is a rapid, non-invasive and well-tolerated ophthalmic imaging technique that has been used to objectively quantify neurodegeneration in adults with metabolic [13][14][15][16][17][18][19][20], cerebrovascular [21][22][23][24] and central neurodegenerative [25][26][27][28] diseases. We have also shown a significant reduction in corneal nerve fibre density, branch density and length in children and adolescents with type 1 diabetes mellitus (T1DM) [29,30] and progression over time [31].…”
Section: Introductionmentioning
confidence: 99%